The Influence of the Preservation Method and Gamma Irradiation Sterilization on TGF-β and bFGF Levels in Freeze-Dried Amnion Membrane (FD-AM) and Amnion Sponge - Heri Suroto, - (Hindawi Publishing Corporation, 2021)
Background. Amnion grafts can be preserved as freeze-dried amnion membrane (FD-AM) and amnion sponge. Preserved grafts require to be sterilized by gamma irradiation. However, each step of the process could affect its biological properties. Even so, there are only a few studies that report the influence of the preservation method and gamma irradiation on growth factor levels in preserved amniotic grafts. Methods. +is was an in vitro experimental study with a pretest-posttest group design using a consecutive sampling technique in one batch of amnion donors at a particular time. +e amnion was made into FD-AM and amnion sponge preparations, and they were sterilized with gamma irradiation (15 kGy and 25 kGy). Nonirradiated specimens served as controls, and 20 mg of each specimen was pulverized to evaluate the growth factors levels using ELISA. Results. +ere were significant decreases in amnion sponge compared to the FD-AM, both in transforming growth factor beta (TGF-β) and basic fibroblast growth factor (bFGF) levels and in the preirradiated and 25 kGy postirradiated preparations (p ≤ 0.05). +e growth factor levels in the preirradiated and postirradiated FD-AM (both 15 kGy and 25 kGy) showed significant differences (p ≤ 0.05). Likewise, the preirradiated amnion sponge group’s growth factor levels compared with the postirradiated amnion sponge group also showed a significant decrease (p ≤ 0.05). Conclusion. TGF-β and bFGF levels were lower in amnion sponge than FD-AM. +e FD-AM and amnion sponge preparations’ growth factors levels were reduced following gamma irradiation sterilization. Although the decrease in growth factor levels is significant, the number of growth factor levels is still sufficient for tissue healing.